Problem-Based Questions to Assess Students’ Critical Thinking on the Topic of Substances and Their Changes - Dwi Septiana Sari; Indri Nurwahidah; Yeni Widiyawati (Postgraduate, University of Mataram, 2025)
21st-century education demands critical thinking skills, which still need to be improved among Indonesian students, especially at the junior high school level. Substance matter and its changes have the potential to train critical thinking through analysis and real problem-solving but are often taught without in-depth understanding. Therefore, the development of problem-based questions is needed to measure and improve students' critical thinking skills. This research aims to develop a problem-based question instrument to measure students' critical thinking skills on substance topics and their changes. This type of research is research and development that involves modifying the Borg & Gall model. The instrument developed is in the form of 30 multiple-choice questions to determine the achievement of students' critical thinking skills. The questions developed are adjusted to critical thinking skills strategies, namely ((1) focus on questions; (2) analyze arguments; (3) ask and answer challenge clarification questions; (4) consider the credibility of a source; (5) observing and considering the results of observations; (6) making deductions and considering the results of deductions; (7) making induction and considering the results of induction; (8) making and evaluating decisions; (9) identifying assumptions; and (10) determining an action. The validation of evaluation experts, subject matter experts, and junior high school science teachers showed that problem-based questions were valid and feasible to measure students' critical thinking skills toward substance material and its transformation